2010
DOI: 10.1055/s-0030-1252035
|View full text |Cite
|
Sign up to set email alerts
|

Regionale Unterschiede der Lebenserwartung in Deutschland auf Ebene der Kreise und kreisfreien Städte und deren möglichen Determinanten

Abstract: The aim of this study is to show health differences at a county level in Germany and to identify possible reasons for these differences. The study calculates life expectancy as being representative for the health status. The analytical part of the study uses a wide database with socioeconomic, environmental, educational and health-care data. In a first step, the set of variables is reduced by a factor analysis and three factors are generated (socioeconomic conditions, environment, health-care). Secondly, a clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 3 publications
3
17
0
2
Order By: Relevance
“…Virtually all of the studies on regional mortality from the 1970s up until today have found an association between high mortality and socioeconomic deprivation in western Germany's regions. Investigations of the relationship between mortality in the German NUTS-3 districts and contextual conditions have revealed a particularly strong association with regional socioeconomic conditions (Brzoska and Razum 2008), even when compared with other factors like the physical environment or health care (Latzitis et al 2011). The strong role of socioeconomic mortality determinants has also been confirmed by several studies contrasting variation across districts or municipalities within a specific federal state (e.g., Kuhn et al 2006;Maier et al 2012;Strohmeier et al 2007).…”
Section: Figure 3 Around Herementioning
confidence: 84%
See 1 more Smart Citation
“…Virtually all of the studies on regional mortality from the 1970s up until today have found an association between high mortality and socioeconomic deprivation in western Germany's regions. Investigations of the relationship between mortality in the German NUTS-3 districts and contextual conditions have revealed a particularly strong association with regional socioeconomic conditions (Brzoska and Razum 2008), even when compared with other factors like the physical environment or health care (Latzitis et al 2011). The strong role of socioeconomic mortality determinants has also been confirmed by several studies contrasting variation across districts or municipalities within a specific federal state (e.g., Kuhn et al 2006;Maier et al 2012;Strohmeier et al 2007).…”
Section: Figure 3 Around Herementioning
confidence: 84%
“…Empirical studies on the (ecological) association between regional mortality and indicators of health care provision have shown that the relationship between regional mortality and the number of physicians or hospital beds per capita is small, or is even counterintuitive (Kibele 2012;Kuhn et al 2006;Latzitis et al 2011). When the concept of avoidable mortality-i.e., mortality which could be prevented with timely and efficient health care-was used as a measure of health care performance and quality of health care, a high correlation with life expectancy across the regions was found (Kibele 2012;Sundmacher et al 2012).…”
Section: Figure 3 Around Herementioning
confidence: 99%
“…These living conditions and persisting sociodemographic and socioeconomic disparities have an impact on the magnitude of health inequalities (John et al 2001;Nolte and McKee 2004;Voigtlander et al 2010). This is also true for West Pomerania, an outlying region in the Federal State Mecklenburg-West Pomerania (Destatis 2010;Völzke et al 2011;Reichert-Schick 2008;Latzitis et al 2011). We assume that especially in this peripheral region of transition and deprivation informal social relations play an important role for coping with socially determined inequalities in health (Nebelung et al 2010;Mackereth and Appleton 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A further specific focus of this study is to examine these associations in the north-east of Germany (Federal State Mecklenburg-West Pomerania), a deprived region characterised by social change, population decrease due to migration, undersupply of medical services, high premature mortality and high prevalence of common risk factors and diseases (Destatis 2010;Statistisches Amt Mecklenburg Vorpommern 2009;Völzke et al 2011;Reichert-Schick 2008;Fendrich and Hoffmann 2007;Latzitis et al 2011). Compared to the general German population, this region is also deprived in terms of socioeconomic characteristics like income, unemployment rate and education (Destatis 2002(Destatis , 2010Destatis and WZB 2011).…”
Section: Introductionmentioning
confidence: 99%
“…So berichten beispielsweise Cummings et al von einem Zusammenhang zwischen dem selbst-eingeschätzten Gesundheitszustand und 6 regionalen sozialen Variablen [ 5 ] . Auch in Deutschland sind einige Studien zum Zusammenhang zwischen regionalem sozialen Status und Gesundheit erschienen [ 7 ] . Maier et al [ 8 ] stellten in einer Studie auf Ebene von Gemeinden einen Zusammenhang zwischen regionaler Depriva tion und Mortalität fest.…”
unclassified